KUALITAS SPERMATOZOA CAUDA EPIDIDIMIS SAPI BALI PADA KELOMPOK UMUR YANG BERBEDA - Angelina Novita Tethool (Jambura Journal of Animal Science, 2023)
Utilization of cauda epididymis spermatozoa has been carried out because these spermatozoa can be used in artificial insemination or in vitro fertilization. The purpose of this study was to obtain information on the quality of spermatozoa which produced from the cauda epididymis of Bali cattle at different ages. The cauda epididymis samples used came from 31 slaughterhouses. Information and identification of the age of the cattle was based on the structure of the incisors. Observations were made on the variables of motility, concentration, viability and abnormalities of spermatozoa. Each variable was observed in duplicate from each cauda. The data was performed using a t-test to obtain differences in each group. The results showed that the motility was 64.1% in 2 years to 71.2% in 3 years. Spermatozoa concentration were increase from 310.1x107/mL to 401.1x107/mL in 3 years. Viability values were 93.8% to 95.9% and total abnormality was 16.2 to 20.6% in 3 years. The results of statistical analysis showed that there was a significant difference (P0.05) for the concentration, viability and head abnormality of the spermatozoa. Based on the results of the study it can be concluded that the quality of spermatozoa cauda epididymis is affected by the age of the Bali cattle. The concentration, viability and head abnormality values were increased with increasing age of Bali cattle.